Community Empowerment in Cajeput Oil Processing in Negeri Buano Utara, Huamual Belakang District, West Seram Regency - Sombalatu, Syukur; Pinoa, Wiclif Sepnath; Riry, Johan (Jurnal Pendidikan Geografi Unpatti, 2022)
Eucalyptus oil management is in North Buona country, Western Seram, with its distillation system facilitated by skilled labor renting eucalyptus tree land. Until the distribution system, that is. There are three shares: one for landowners, one for the eucalyptus oil refinery, and the land owner himself. This type of research is field research through descriptive qualitative research that produces data in words written or spoken by people and actors with theoretical observations. The data used are primary, namely direct interviews, while the secondary data was obtained from the North Buona District Office. This research shows that community empowerment through Eucalyptus oil management in North Buona Village, Huamual District, behind the western part of the district of Seram, turns out that it has a selling value and very high income to manage the welfare of the community and family and other needs.